1890 W. Va. Acts 173, ch. 14 - (:unkn) unknown (My University, 1890)
And it shall be unlawful for any person by the use of any swivel or pivot gun, or any other than the common shoulder gun, or by the aid of any push boat, or sneak boat, used for carrying such gun, to catch, kill, wound or destroy, or to pursue with such intent upon any of the waters, bogs . . . or any cover to which wild fowl resort within this State, any wild goose, wild duck or brant.
Keywords: HUNTING REGULATION